2014
DOI: 10.4172/2157-7439.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-based Transdermal System for Fluconazole Skin Delivery

Abstract: The development of a controlled-release dosage form of antifungals is of crucial importance in view of the side-effects of conventional oral and intravenous treatments of Sporotrichosis. In this study, systems composed of polyoxypropylene (5) polyoxyethylene (20) cetyl alcohol (PPG-5-CETETH-20) as a surfactant, oleic acid as an oil phase, and water were developed as a possible fluconazole transdermal drug delivery system. The systems were characterised by polarised light microscopy (PLM), SAXS, and rheological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…These findings are correlated with other results from our group that determined the drug kinetics in liquid crystalline matrices composed of PPG-5-CETETH-20, OA, and water [ 14 , 25 ]. Carvalho et al (2009) determined that the zidovudine kinetics in the lamellar phase decrease the drug release considerably when compared with a microemulsion made of the same components [ 25 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are correlated with other results from our group that determined the drug kinetics in liquid crystalline matrices composed of PPG-5-CETETH-20, OA, and water [ 14 , 25 ]. Carvalho et al (2009) determined that the zidovudine kinetics in the lamellar phase decrease the drug release considerably when compared with a microemulsion made of the same components [ 25 ].…”
Section: Resultssupporting
confidence: 90%
“…Most of the surfactant-based liquid crystals reported in the literature are composed of glycerol monooleate [ 10 , 11 ]. Recently, we demonstrated the use of a polyoxypropylene (5) polyoxyethylene (20) cetyl alcohol (PPG-5-CETETH-20) surfactant-based system as a potential mucoadhesive agent for nasal and topical applications [ 12 , 13 , 14 ]. The oily phases including oleic acid (OA) and mineral oil play a major role in the behavior of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, it has been shown the interest in the development of surfactant systems, such as liquid crystalline systems (LCSs) and microemulsions (MEs) for topical drug delivery. Since surfactants have the ability to stabilize components with different polarities, additional regions for the solubilization of hydrophilic and lipophilic drugs are created [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several studies have shown that lamellar-, hexagonal-, or cubic-mesophase-based formulations are capable of penetrating the skin and act as good candidates for topical drug delivery systems. 5,15,16,[34][35][36][37] …”
Section: Introductionmentioning
confidence: 99%